Assessment of the use of outputs from PIM-supported work on national SAMs and CGE models - Somwaru, Agapi (International Food Policy Research Institute, 2021)
This report evaluates the outputs from the CGIAR Research Program on Policies, Institutions, and Markets (PIM) on national social accounting matrices (SAMs) and single-country computable general equilibrium (CGE) models. The study aims to identify what policies, programs, strategies, and expenditure decisions were informed by SAMs and single-country CGE models. The report seeks to document what decisions were made based on the contribution of SAM/CGE models’ outputs that effectively shaped work or what changes were made because of CGIAR PIM– supported economywide modeling being available to decision makers. Based on the above, the report makes recommendations for CGIAR PIM–supported single economywide modeling work on how to effectively increase decision makers’ use of SAM/CGE outputs.